Analisis Defect pada Proses Produksi Mie Blok dengan Metode SPC dan RCA Pada PT. Lestari Alam Segar - Mariras Sitepu; Abdul Aziz Syarif; Uun Novalia Harahap (CV. IRA PUBLISHING, 2023)
PT. Lestari Alam Segar is a food industry company that manufactures instant noodles on Jalan Pulau Pinang III Kav. 600-342 E Ex. Saentis Kec. Percut sei Tuan, Kab. Deli Serdang, North Sumatra. PT. Lestari Alam Segar produces around 45,000 boxes per day. The purpose of this problem is to control the quality of finished products and identify the causes of product quality deviations using statistical tools, namely seven tools (check sheet, histogram, Pareto diagram, cause and effect diagram, scatter diagram, process flow diagrams, and control charts) so that it can determine the factors that cause product defects and the prevention that will be carried out. The conclusion of this study is that of the seven quality control tools that have been analyzed; it can be seen that the cause of quality deviation at PT. Lestari Alam Segar of the many product defects that occur, the most defective products are burnt noodles caused by three factors, namely humans, methods, and machines and preventive measures that can be taken from the human factor are providing strict direction and supervision and conducting training for operators.